An upgrade of the SCANDAL setup for measurements of elastic neutron scattering at 175 MeV - P. Andersson (2018)
The experimental setup SCANDAL, used for measurements of the differential cross section for elastic and inelastic neutron scattering, has recently been upgraded with larger CsI scintillating detectors to enable measurements at energies up to 175 MeV. Measurements on Fe, Bi and Si have been carried out using the quasi mono-energetic neutron beam at the The Svedberg Laboratory, and data is under analysis. The experimental setup can be used for measurements on a wide range of target nuclei, including C and O, which are important for dosimetry applications. SCANDAL can also run in proton mode, for measurements of the (n,p) reaction. This paper describes the new experimental setup, and reports on its properties, such as energy resolution. © 2010 Published by Elsevier Ltd. All rights reserved.